Comparison Between Two-Level Converter and Three-level NPC Converter for Evaluation the Quality Power of DFIG Based Wind Turbines - Zerzouri Nora; Labar Hocine; Kechida Sihem (Institute of Advanced Engineering and Science, 2015)
This paper deals the power control for three-level voltage source inverter NPC-VSI feeds the rotor of the doubly fed induction generator ‘DFIG’ based wind power generation system. This converter allows controlling the rotor voltage in magnitude and phase angle with a high flexibility and can therefore be used for active and reactive power control of DFIG. The control is especially designed to reduce the harmonic distortion of the generated currents and active power ripples of the classical control. In addition, it’s convenient for high power drive and variable speed generator applications with constant switching frequency. The detailed operation principle and simulation results for 3 MW of DFIG are also discussed.